2014
DOI: 10.3390/children1030355
|View full text |Cite
|
Sign up to set email alerts
|

Health Behaviors of Childhood Cancer Survivors

Abstract: There has been a dramatic increase in the number of childhood cancer survivors living to an old age due to improved cancer treatments. However, these survivors are at risk of numerous late effects as a result of their cancer therapy. Engaging in protective health behaviors and limiting health damaging behaviors are vitally important for these survivors given their increased risks. We reviewed the literature on childhood cancer survivors’ health behaviors by searching for published data and conference proceedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
3
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 125 publications
1
30
3
2
Order By: Relevance
“…It is likely that adherence to physical activity guidelines remains moderate in early survivorship and then declines as survivors age into adulthood. However, the factors examined in our study did not predict a change in physical activity in early survivorship, despite correlational findings in prior research . This may be due to timing.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…It is likely that adherence to physical activity guidelines remains moderate in early survivorship and then declines as survivors age into adulthood. However, the factors examined in our study did not predict a change in physical activity in early survivorship, despite correlational findings in prior research . This may be due to timing.…”
Section: Discussioncontrasting
confidence: 99%
“…Achievement of recommended levels of physical activity was moderate for high intensity exercise and poor for low intensity exercise. Reviews report that approximately 50% of survivors or less achieve recommendations for physical activity and/or exercise . Although few studies have specifically reported low‐ and high‐intensity physical activity levels in survivors of this age group, our finding of more survivors meeting recommendations for high intensity exercise than for low intensity exercise contradicts previous findings .…”
Section: Discussioncontrasting
confidence: 97%
See 3 more Smart Citations